Orthogonal Peptide‐Templated Labeling Elucidates Lateral ETAR/ETBR Proximity and Reveals Altered Downstream Signaling. (26th October 2021) - Wolf, Philipp; Mohr, Alexander; Gavins, Georgina; Behr, Victoria; Mörl, Karin; Seitz, Oliver; Beck‐Sickinger, Annette G.
Abstract: Fine‐tuning of G protein‐coupled receptor (GPCR) signaling is important to maintain cellular homeostasis. Recent studies demonstrated that lateral GPCR interactions in the cell membrane can impact signaling profiles. Here, we report on a one‐step labeling method of multiple membrane‐embedded GPCRs. Based on short peptide tags, complementary probes transfer the cargo (e. g. a fluorescent dye) by an acyl transfer reaction with high spatial and temporal resolution within 5 min. We applied this approach to four receptors of the cardiovascular system: the endothelin receptor A and B (ETA R and ETB R), angiotensin II receptor type 1, and apelin. Wild type‐like G protein activation after N‐terminal modification was demonstrated for all receptor species. Using FRET‐competent dyes, a constitutive proximity between hetero‐receptors was limited to ETA R/ETB R. Further, we demonstrate, that ETA R expression regulates the signaling of co‐expressed ETB R. Our orthogonal peptide‐templated labeling of different GPCRs provides novel insight into the regulation of GPCR signaling. Abstract : GPCR‐GPCR interactions can influence signaling events but are difficult to investigate in live cell setups. Here, we report on an orthogonal labeling approach, which excludes intracellular background signals and allows the installment of different dyes. Using this technique, the interaction of homo‐receptors demonstrated for different GPCRs, but hetero‐interaction was limited to ETA R/ETB R. For the latter, impaired ETB R signaling was shown.